Peran Protokoler dan Kehumasan pada Secretariat Daerah Kabupaten Pohuwato (Studi Kasus Sekretariat Daerah Kabupaten Pohuwato) - Aprilani Parengring; Fobigyardjo Humokor (Universitas Islam Darul Ulum Lamongan, 2024)
The objective of this study is to obtain an overview of the Role of Protocol and Public Relations in the Regional Secretariat of Pohuwato Regency. This research employs a qualitative descriptive approach. Data collection techniques include in-depth interviews with several informants, observations, and the recording of secondary data related to the research problem. The research findings conclude that the Role of Protocol and Public Relations in the Regional Secretariat of Pohuwato Regency has not yet been fully optimized. As a government institution or public body, the Pohuwato Regency Government is obligated to provide open and transparent information to the public. The role of public relations, which includes acting as the government's voice to the public and ensuring that public voices are heard by the government through various communication media, has not been effectively implemented. Another key function of public relations is as a public communication tool. The Public Relations and Protocol Division of the Regional Secretariat of Pohuwato Regency has carried out four essential roles: communicator, facilitator, information disseminator, and catalyst, to ensure comprehensive information distribution. It is recommended that, in carrying out its duties and functions, the Public Relations Division of Pohuwato Regency should be able to apply and understand organizational communication as a communication process conducted by the organization towards all its stakeholders. Establishing a reciprocal relationship between the organization and its public is a fundamental principle that must be upheld. Public relations should function as a two-way communication process with the public to support management functions and objectives by enhancing cooperation and fulfilling shared interests. Public relations staff must be able to ensure that messages are effectively understood by others in order to maintain the reputation and image of the institution they represent.